PENDAPATAN DAN RISIKO USAHATANI UBI KAYU (Manihot utilisima) DI DESABUMI AGUNG MARGA KECAMATAN ABUNG TIMUR KABUPATEN LAMPUNG UTARA - Othi Pratiwi; Dwi Haryono; Zainal Abidin (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to analyze income, price and production risks, and farmer behavior on the risk of cassava farming. This research is a survey research, carried out in Bumi Agung Marga Village, Abung Timur Distric of North Lampung Regency in February 2018. There are 46 samples of cassava farmers who were chosen randomly. Farm income is analyzed by income analysis, whereas price risk and production risk are analyzed by coefficient of variation analysis. To determine the behavior of farmers against risk is used quadratic utility function analysis. The research results showed that cassava farming was profitable in which income value was Rp15, 146,206.10/ha and R/C was 3.30. The production risk had a CV value of 0.057 and L 20.061; it meant that the production risk was low, because the result of CV <0.5 and L>1. The price risk had a CV value of 0.135 and L 644.695; it meant that the risk was low because the CV <0.5 and L>1. All cassava farmers behave neutral in facing the risk of cassava farming.Key words: cassava, farming, income,risk